TMPO-AS1 is an independent prognostic factor for patients with laryngeal squamous cell carcinoma - Zhang,Lihua (2020)
SUMMARY OBJECTIVE Long noncoding RNA (lncRNAs) are frequently abnormally expressed in tumors and involved in the occurrence and progression of human cancer. Recently, a disease-related lncRNA, TMPO antisense RNA 1 (TMPO-AS1), was identified to be dysregulated in several tumors. Hence, we aimed to demonstrate whether TMPO-AS1 could be a promising prognostic marker for patients with laryngeal squamous cell carcinoma (LSCC). METHODS RT-PCR was performed to test TMPO-AS1 expressions in 187 LSCC specimens compared with matched normal specimens. Chi-squared tests were used to determine the associations between TMPO-AS1 expressions and the clinicopathological characteristics of LSCC patients. Then, the clinical outcome of LSCC patients who had lower or higher TMPO-AS1 expression was analyzed using Kaplan-Meier assays. Finally, a Cox proportional hazards model was carried out to evaluate the prognostic values of TMPO-AS1 and other clinical features. RESULTS We found that TMPO-AS1 was distinctly upregulated in human LSCC tissues compared with corresponding normal specimens (p < 0.01). Higher expressions of TMPO-AS1 were observed to be positively associated with the clinical stage (p = 0.020) and lymph node metastasis (p = 0.027). A clinical study in 187 patients revealed that patients with TMPO-AS1 low expressions had poorer survival than those with TMPO-AS1 high expressions (p = 0.0012). In addition, the result of multivariate assays demonstrated TMPO-AS1 expression is an independent predictor for the overall survival of LSCC patients. CONCLUSIONS TMPO-AS1 might be considered a novel molecule involved in LSCC progression, which provides a possible prognostic biomarker.